Integration of Artificial Light and Solar Power System for Optimizing the Growth of Pakcoy (Brassica rapa L.) in a Hydroponic System - Eka Putri, Renny; Arini, Fahreza; Hasan, Ahsadi (The Journal of Experimental Life Science, 2026)
The demand for energy-efficient and sustainable agricultural systems is increasing in response to limited arable land and rising food needs. This study aims to evaluate the performance of a solar power system (PLTS) as an energy source in a Nutrient Film Technique (NFT) hydroponic system, assess the effectiveness of artificial lighting powered by PLTS on the growth of pakcoy (Brassica rapa L.), and analyze the technical and economic aspects of the system. An experimental method was used, involving the design and installation of the PLTS and artificial lighting system, energy performance testing, and observation of plant growth parameters over 27 days. The experiment compared the growth of pakcoy cultivated in an NFT system with artificial lighting against a control group grown conventionally without additional lighting. The results showed that the integration of artificial light powered by PLTS enhanced photosynthetic efficiency, as indicated by increased plant height, number of leaves, and leaf dimensions compared with the control. The system also proved to be energy-efficient, with an average solar panel efficiency of 12.98%, peak input power of 3,030.80 W.m-2, and peak output power of 287 W.m-2. The average solar radiation intensity received was 333.26 W.m-2. Overall, the integration of artificial lighting with a solar power system has significant potential to support the development of sustainable hydroponic agriculture.